Follicular dynamics, corpus luteum growth and regression in multiparous buffalo cows and buffalo heifers (2014)
Objective. Characterize the follicular dynamics and luteal growth and regression pattern of multiparous (MB) and heifer (BH) Murrah buffaloes in Colombian tropical conditions. Material and methods. Ten MB and ten BH were synchronized with a progesterone-releasing intravaginal device. No artificial insemination was performed during the estrous and daily ultrasound examinations were performed 15 days later to determine the number and diameter of the structures present in both ovaries in the subsequent natural estrous cycle. The Student's T test was used to evaluate differences between MB and BH. All data are presented as mean ± standard deviation. Results. The length of the estrous cycle was 22.00±4.50 days for MB and 22.00±2.70 days for BH. Follicular growth occurs in one (n=1; 5.89%), two (n=14; 82.35%) or three waves (n=2; 11.76%). The first wave initiated the day after ovulation with the recruitment of 8.33±2.06 and 10.00±2.72 follicles in MB and BH, while the second wave started on day 11.00±2.00 and 10.50±2.82, presenting 8.37±2.26 and 8.00±1.51 follicles. The third wave began on day 16.21±3.10 showing 6.50±1.70 follicles, only BM had three waves. The maximum luteal diameter was 19.58±4.16 mm and 17.74±3.32 mm respectively. There were no significant differences between the groups for these variables. Conclusions. These results show that the follicular development in buffaloes occurs in waves, where two waves is the most common pattern, as previously reported by other authors.